Conservation of the 20th century architectural and industrial heritage : international symposium, 18-19.05.2002, İstanbul = Conservation du patrimoine architectural et industriel du 20ème siècle : symposium international, 18-19.05.2002, İstanbul (İstanbul)
182 s.